Analysis of The Language Functions By The Main Characters In The Mean Girls (2004) Movie - Sirait, Hanna Jesica; Pasaribu, Tiara Kristina; Elfrida, Rotua (Lembaga Riset dan Inovasi Almatani, 2025)
In everyday life, humans are never separated from communication. One of the tools used to communicate is language. Language has many functions that can be found in various media, one of which is a movie. When watching movie, without realizing it, most people only watch scenes and listen to dialogue conversations in the movie and do not notice how the functions of language are used. This is why this study was conducted. By choosing Mean Girls movie as the object, this study aimed to discover the types of language functions used by the main characters and how language functions were realized in the Mean Girls movie. This study used mixed methods, quantitative and qualitative methods. The data analysis technique consisted of identifying the transcribed dialogues by the main characters, Cady Heron, Regina George, Janis Ian, Gretchen Wieners, and Karen Smith, using Geoffrey Leech's (1981) theory of language functions. The results show that in Mean Girls movie, five language functions are found. Expressive function is the most used which contains 135 utterances, followed by informative function with 90 utterances, directive function with 75 utterances, phatic function with 17 utterances and the least used is aesthetic function with 2 utterances. The realization is that there are five types of language functions, namely the informative function (when the main characters provide some factual information, actions, place, and direction using language that can be understood by the interlocutors without confusion). Directive function (when the main characters asked favour, command, give order, invite, and request, so that the listeners follow the wishes of the main characters). Expressive function (when the main characters use this function to express their feelings and emotions such as amazement, judgment, anger, falling in love, and happiness). Phatic function (when the main characters use this function to maintain a good social relationship with the recipients). And finally, aesthetic function (when the main characters use the function by prioritizing the beauty of language yet the meaning is still conveyed to produce a sensory or emotional experience of the recipients). So, it can be concluded that language functions can be found anywhere, including in the movies and moreover, language functions cannot be avoided from everyday life.